College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 1 - Equations and Inequalities - Exercise Set 1.6 - Page 178: 13



Work Step by Step

Square both sides and put all terms on one side to create a quadratic equation. Then use trial and error to factor it, and set the values found equal to zero. One of the solutions does not work. $\sqrt {x+3}=x-3$ $(\sqrt {x+3})^2=(x-3)^2$ $x+3=x^2-6x+9$ $x^2-7x+6=0$ $(x-1)(x-6)=0$ $x=1,6$ $\sqrt {1+3}\ne1-3$ $x=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.